(untitled) (Research, Society and Development, 2020)
The objective was to analyze the scientific evidence in the literature about the prevention of pneumonia associated with mechanical ventilation in intensive care units. It is an integrative review type research. The search for the articles took place during the period from March / 2016, with a time frame from 2011 to 2015, and took place through the electronic bases of MEDLINE, LILACS, BDENF and IBECS, using Decs / Mesh: Ventilation-Associated Pneumonia as controlled descriptors. Mechanics, Prevention and Control, Intensive Care Units. Ten articles were selected and analyzed for the final sample, which met the inclusion criteria and answered the research question. After analysis, the results were presented in two categories: Importance and challenges of Control and Prevention Measures; and Description of the specific measures recommended for the prevention of VAP. Pneumonia associated with MV is one of the main diseases that affect the health of patients in intensive care. Thus, it is necessary that preventive measures and strategies are adopted by the professionals who make up the teams in the ICU sector, in order to reduce the high rates of pneumonia in this environment. In addition, it is necessary to develop further research, which will help in the development and implementation of new actions, which will lead to improvement in care, in relation to the topic addressed, as well as collaborating for quality and safety to the health of patients who need this care. .